COVID-19 Pandemic: The Role of the Anaesthesiology Resident in the Education and Safety of Health Professionals - Vieira, Ana; Infante, Cândida; Mendes, Eunice; Castro, Mafalda; Asseiro, Mariana; Camões, Pedro; Norte, Gustavo; Bernardino, Ana (Journal of the Portuguese Society of Anesthesiology, 2020)
Introduction: In a public health crisis, as the one caused by SARSCoV- 2, hospital staff are the frontline in the response of healthcare system and their safety should be a priority. The purpose of this paper is to argue the role of Anaesthesiology residents in the training and overall safety of healthcare professionals during COVID-19 pandemic. Material and Methods: Descriptive retrospective study on training methodology used by a group of anesthesiologists. doctors and residents. The project started on March 16th 2020 to date in a University Hospital Center. Results: The anaesthesiologists residents collaborated in the building of cognitive resources and taught how and when to use correctly a personal protection equipment (PPE). In total 248 professionals were trained: 98 anaesthesiology doctors, 15 doctors from other departments, 75 nurses, 30 health assistants and 40 technicians. Discussion: COVID-19 outbreak changed radically the world and consequently healthcare staff reality, who are taken a significant risk of contracting the infection. This new life represents a huge challenge in terms of biological safety. Evidence shows that a correct use of PPE reduces the transmission rate and protects the team, so it is of paramount that each of those involved take their vital role to decrease the spread of the disease. Conclusion: Anaesthesiology doctors and resident had a huge involvement in the training staff process, contributing this way for the reduction of the infection and spread of the disease.